2021
DOI: 10.3389/fmed.2021.622225
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Glucocorticoids in Lupus Nephritis: New Pathways for an Old Drug

Abstract: Glucocorticoids therapy has greatly improved the outcome of lupus nephritis patients. Since their discovery, their adverse effects have counterbalanced their beneficial anti-inflammatory effects. Glucocorticoids exert their effects through both genomic and non-genomic pathways. Differential activation of these pathways is clinically relevant in terms of benefit and adverse effects. Ongoing aims in lupus nephritis treatment development focus on a better use of glucocorticoids combined with immunosuppressant dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 113 publications
(28 reference statements)
0
28
1
2
Order By: Relevance
“…NSAIDs, for example, are famous for their counter vasodilatation effect through the inhibition of the cyclooxygenase enzyme, leading to a hemodynamically mediated acute and chronic kidney injury [ 82 , 83 ]. Corticosteroids, on the other hand, although already used for the treatment of many inflammatory kidney disorders, such as IgA nephropathy, lupus nephritis, and interstitial nephritis [ 84 , 85 , 86 ], are known for their long-term and severe side-effects, which impact the kidneys—among other organs—and may hinder their consideration as a lifelong treatment, even in low doses, for nephropathic cystinosis. To this date, no prospective therapeutic clinical trial has been conducted to address the inflammatory aspect of cystinosis in human patients.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…NSAIDs, for example, are famous for their counter vasodilatation effect through the inhibition of the cyclooxygenase enzyme, leading to a hemodynamically mediated acute and chronic kidney injury [ 82 , 83 ]. Corticosteroids, on the other hand, although already used for the treatment of many inflammatory kidney disorders, such as IgA nephropathy, lupus nephritis, and interstitial nephritis [ 84 , 85 , 86 ], are known for their long-term and severe side-effects, which impact the kidneys—among other organs—and may hinder their consideration as a lifelong treatment, even in low doses, for nephropathic cystinosis. To this date, no prospective therapeutic clinical trial has been conducted to address the inflammatory aspect of cystinosis in human patients.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…All the patients received 500 mg daily intravenous methylprednisolone as pulse therapy for 3 successive days and 0.6 mg/kg oral prednisone as maintenance treatment. After 6 months, the overall response rate in both groups was higher than 60% (5). A systematic review demonstrated that in comparison to the oral steroid-treated or untreated group, intravenous pulse corticosteroid therapy did not increase the risk of adverse effects, including neuropsychiatric, metabolic effect, and infectious complications (12).…”
Section: Discussionmentioning
confidence: 97%
“…Los glucocorticoides tienen dos vías de acción, una vía genómica y otra no genómica (39) , con un perfil diferente en cuanto a sus mecanismos de activación y de seguridad (40) . La vía genómica se activa a partir de dosis bajas de PDN o equivalente, menores de 7,5 mg/d, y expresa su efecto antiinflamatorio en forma dosis dependiente, alcanzando una saturación cercana al 100% con dosis de 30-40 mg/d.…”
Section: Discussionunclassified